Spinopelvic characteristics normalize 1 year after total hip arthroplasty: a prospective, longitudinal, case-controlled study - Innmann, Moritz Maximilian; Verhaegen, Jeroen C. F.; Reichel, Franz; Schaper, Bibiane; Merle, Christian; Grammatopoulos, George (The journal of bone & joint surgery. A, American volume, 2022)
Background: The presence of hip osteoarthritis is associated with abnormal spinopelvic characteristics. This study aimed to determine whether the preoperative, pathological spinopelvic characteristics normalize at 1 year after total hip arthroplasty (THA). Methods: This was a prospective, longitudinal, case-control, matched cohort study. Forty-seven patients undergoing THA underwent preoperative and 1-year postoperative assessments. This group was matched with regard to age, sex, and body mass index with 47 controls (volunteers) with well-functioning hips. All participants underwent clinical and radiographic assessments including lateral radiographs in standing, relaxed-seated, and deep-flexed-seated positions. Spinopelvic characteristics included change in lumbar lordosis (ΔLL), change in pelvic tilt (ΔPT), and hip flexion (change in pelvic-femoral angle, ΔPFA) when moving from a standing position to either of the seated positions. Spinopelvic hypermobility was defined as ΔPT > 30° between the standing and upright-seated positions. Results: Patients who underwent THA, compared with the control group, preoperatively demonstrated less mean change in hip flexion (ΔPFA, −54.8° ± 17.1° compared with −68.5° ± 9.5°; p < 0.001), greater mean change in pelvic tilt (ΔPT, 22.0° ± 13.5° compared with 12.7° ± 8.1°; p < 0.001), and greater mean lumbar movement (ΔLL, −22.7° ± 15.5° compared with −15.4° ± 10.9°; p = 0.015) transitioning from a standing position to an upright-seated position. After THA, these differences were no longer present between the THA group and the control group: the mean postoperative changes were −65.8° ± 12.5° (p = 0.256) for ΔPFA, 14.3° ± 9.5° (p = 0.429) for ΔPT, and −15.3° ± 10.6° (p = 0.966) for ΔLL. The higher prevalence of spinopelvic hypermobility in the THA group compared with the control group that was observed preoperatively (21% compared with 0%; p = 0.009) was no longer present after THA (6% compared with 0%; p = 0.194). Similar results were found moving from a standing position to a deep-seated position after THA. Conclusions: Preoperative spinopelvic characteristics that contribute to abnormal mechanics can normalize after THA following improvement in hip flexion. This leads to patients having the expected hip, pelvic, and spinal flexion as demographically matched controls, thus potentially eliminating abnormal mechanics that contribute to the development or exacerbation of hip-spine syndrome. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.
Gesehen am 18.07.2022